The Peripersonal Space in a social world. (September 2021) - Bogdanova, Olena V.; Bogdanov, Volodymyr B.; Dureux, Audrey; Farnè, Alessandro; Hadj-Bouziane, Fadila
Abstract: The PeriPersonal Space (PPS) has been defined as the space surrounding the body, where physical interactions with elements of the environment take place. As our world is social in nature, recent evidence revealed the complex modulation of social factors onto PPS representation. In light of the growing interest in the field, in this review we take a close look at the experimental approaches undertaken to assess the impact of social factors onto PPS representation. Our social world also influences the personal space (PS), a concept stemming from social psychology, defined as the space we keep between us and others to avoid discomfort. Here we analytically compare PPS and PS with the aim of understanding if and how they relate to each other. At the behavioral level, the multiplicity of experimental methodologies, whether well-established or novel, lead to somewhat divergent results and interpretations. Beyond behavior, we review physiological and neural signatures of PPS representation to discuss how interoceptive signals could contribute to PPS representation, as well as how these internal signals could shape the neural responses of PPS representation. In particular, by merging exteroceptive information from the environment and internal signals that come from the body, PPS may promote an integrated representation of the self, as distinct from the environment and the others. We put forward that integrating internal and external signals in the brain for perception of proximal environmental stimuli may also provide us with a better understanding of the processes at play during social interactions. Adopting such an integrative stance may offer novel insights about PPS representation in a social world. Finally, we discuss possible links between PPS research and social cognition, a link that may contribute to the understanding of intentions and feelings of others around us and promote appropriate social interactions.